Oral Health Preventive Program in Patients with Autism Spectrum Disorder - Elisabetta Carli; Marco Pasini; Francesca Pardossi; Isabella Capotosti; Antonio Narzisi; Lisa Lardani (MDPI AG, 2022)
The aim of the study was to evaluate clinical hygienic parameters, patient collaboration, and dental habits in patients with ASD (autism spectrum disorder) before and after a tailored prevention program. A total of 100 patients (78 males and 22 females, mean age 8 ± 0.7 years old) was recruited, with ages ranging from 7 to 16 years old, and diagnoses of ASD. We evaluated the plaque index (IP), gingival index (IG), the dmft/DMFT, the frequency of tooth brushing, and the frequency of snacks for each patient. Patient behaviour was evaluated with the Frankl scale, and each patient was individually reassessed after five visits from the first one by the same operator. The t test was used to compare the parameters before and after the inclusion in the dedicated dental pathway. From T1 to T2 we found a significant improvement of the IP (p < 0.001), IG (p < 0.001), and the frequency of tooth brushing (p < 0.001). Concerning the frequency of snacks and the parameter dmft/DMFT, the differences in the observed averages were not significant (p > 0.05). The difference in collaboration between T1 and T2 evaluated by the Frankl scale was statistically significant (p < 0.001). It was found that the prevention program allowed a significant improvement in both clinical parameters and patient behaviour. The personalized digital supports can have a key role for success in familiarization and desensitization processes of patients affected by ASD, leading an increase in their collaboration.